Accordo bilaterale per gli anni accademici 2011/2013 programma LLP/ Erasmus Università degli Studi di Firenze e Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme. - Subject area: Architecture, urban and regional planning; Law; Psychology and Behavioural Sciences